Impact of Collaborative Innovation Capability and Emotional Intelligence on Sustainable Innovation Performance with Mediation of Employee Burnout - Malik, Dr. Muhammad Shaukat; Mohsin, Iqra (The journal of contemporary issues in business and government, 2022)
Purpose – This study was conducted to find out the impact of emotional intelligence and collaborative innovation capability on sustainable innovation performance and to know whether the organizational culture moderates and employee burnout mediates this relationship or not. Design/Methodology/Approach –The researcher adopted cross sectional and quantitative research design to fulfill this study’s objectives. Owing to Covid- 19 pandemic, online survey was conducted through questionnaire for data collection of 300 employees who are currently working in Telecom Industry of Pakistan. As a statistical tool, Smart PLS (Partial Least Square) v.3 was run by adopting the Structural Equation Modeling (SEM) to find out the direct and indirect effects among the variables while the descriptive statistics were employed by using SPSS v.20. Findings – The proposed hypothesized relationship of this study was found supported wherein positive and significant relationships were found among organizational culture, emotional intelligence and collaborative innovation capability on sustainable innovation performance while between the sustainable innovation performance and employee burnout, a negative relationship was found. Originality/value – Along with new dimensions and locality, the current study was a first attempt to provide the practitioners, policy makers and researchers to understand the issues of Sustainable Innovation Performance related to the employees’ Emotional Intelligence and their Collaborative Innovation Capability with the main focus of mediation role of Employee Burnout and moderating role of Organizational Culture.